The influence of gap size on plant species diversity and composition in beech (Fagus orientalis) forests, Ramsar, Mazandaran Province, North of Iran - HASSAN POURBABAEI; HAMIDREZA HADDADI-MOGHADDAM; MARZIEH BEGYOM-FAGHIR; TOOBA ABEDI (Society for Indonesian Biodiversity, 2013)
Pourbabaei H, Haddadi-Moghaddam H, Begyom-Faghir M, Abedi T. 2013. The influence of gap size on plant species diversity and composition in beech (Fagus orientalis) forests, Ramsar, Mazandaran Province, North of Iran. Biodiversitas 14: 89-94.This study was conducted to investigate the influence of gap size on plant species diversity and composition in beech 2 micro-plots within the gaps. Diversity indices including Shannon-Wiener, Simpson, Mc Arthur's N1 , Hill's N, species richness and Smith-Wilson’s evenness index were computed. The results revealed that there was significant difference among three gap categories in terms of diversity. The highest diversity values of tree and herbaceous species were obtained in the large gaps, while the highest diversity value of shrub species was in the medium gaps. Species composition of small gaps (28 species: 7 trees and 21 herbaceous), medium gaps (37 species: 7 trees, 5 shrubs and 25 herbaceous) and large gaps (40 species: 7 trees, 4 shrubs and 29 herbaceous) were recognized. Therefore, based on the results of this study, it is recommended that in order to maintain plant diversity and composition up to 400 m gap size cloud be used in this forests.